2022
DOI: 10.1039/d2qm00604a
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-modified g-C3N4and its photocatalytic applications

Abstract: As an emerging semiconductor-based catalyst, g-C3N4 has attracted significant attention in visible-light-driven photocatalytic energy conversion, synthesis of chemicals, and environmental remediation. While pristine g-C3N4 exhibits a weak response to visible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 174 publications
1
18
0
Order By: Relevance
“…As seen in Figure d, an additional absorption band known as the Urbach tail ranging from 450 to 600 nm is formed in N v CN, and the absorption edge at around 470 nm is blue-shifted to 450 nm in the case of C v CN compared to CN. With longer wavelength, a red shift in the Urbach tail edge is observed with increasing nitrogen vacancies, and for carbon vacancies, a blue shift in light absorption edge is usually reported . For aNi-MOF, an intense absorption band centered at 455 nm is observed due to the 3 T 1 (F) → 3 A 2 (P) d–d transition.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As seen in Figure d, an additional absorption band known as the Urbach tail ranging from 450 to 600 nm is formed in N v CN, and the absorption edge at around 470 nm is blue-shifted to 450 nm in the case of C v CN compared to CN. With longer wavelength, a red shift in the Urbach tail edge is observed with increasing nitrogen vacancies, and for carbon vacancies, a blue shift in light absorption edge is usually reported . For aNi-MOF, an intense absorption band centered at 455 nm is observed due to the 3 T 1 (F) → 3 A 2 (P) d–d transition.…”
Section: Resultsmentioning
confidence: 92%
“…With longer wavelength, a red shift in the Urbach tail edge is observed with increasing nitrogen vacancies, and for carbon vacancies, a blue shift in light absorption edge is usually reported. 50 For aNi-MOF, an intense absorption band centered at 455 nm is observed due to the 3 T 1 (F) → 3 A 2 (P) d−d transition. Furthermore, a broader and stronger absorption tail, starting at ≈550 nm and extending to the near-IR (NIR) region (800−1400 nm), is also clearly observed for the g-C 3 N 4 /aNi-MOF composites (C v CN/aNi, CN/aNi, and N v CN/aNi).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Generally, TiO 2 and C 3 N 4 are promising UV and visible-response semiconductors and widely useful photosensitizers. [71][72][73] However, without any cocatalyst, individual TiO 2 and C 3 N 4 showed lower hydrogen production (Fig. 4(a)), possibly due to the sluggish hydrogen evolution kinetics.…”
Section: Photocatalytic Activity and Stability Of Cocatalystsmentioning
confidence: 99%
“…9,10 At present, the research on photocatalysts is mainly affected by insufficient visible light absorption, low charge separation efficiency, and instability caused by photo-corrosion. In numerous reports, we found that Zn 0.5 Cd 0.5 S, 11 Mn x Cd 1− x S, 12,13 black TiO 2 , 14 and C 3 N 4 15 were the widely explored photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 At present, the research on photocatalysts is mainly affected by insufficient visible light absorption, low charge separation efficiency, and instability caused by photo-corrosion. In numerous reports, we found that Zn 0.5 Cd 0.5 S, 11 Mn x Cd 1−x S, 12,13 black TiO 2 , 14 and C 3 N 4 15 were the widely explored photocatalysts. As an ideal candidate, the ternary solid solution of a typical Cd x Zn 1−x S with a tunable bandgap and band position has been extensively studied and reported.…”
Section: Introductionmentioning
confidence: 99%